Profile measurements of snow transport and micrometeorology at Mizuho Station in Antarctica ... - Nishimura, Kouichi; Sigmund, Armin; Melo, Daniela Brito; Lehning, Michael (EnviDat, 2024)
This data was collected at Mizuho Station (44.315°E, 70.71°S, 2230 m a.s.l.), East Antarctica, from **30 September to 22 November 2000** during the 41st Japanese Antarctic research expedition. Vertical profiles of the horizontal mass flux and particle number size distribution of drifting and blowing snow were measured in the lowest 10 m of the atmosphere using four **snow particle counters** (SPCs). Three 3-dimensional **ultrasonic anemometers** were deployed in the lowest 25 m of the atmosphere to record the wind velocity components and sonic temperature at a high frequency of 100 Hz. Additionally, an **automatic weather station** provided air temperature, relative humidity, air pressure, shortwave and longwave downward and upward radiation fluxes, surface temperature, snow temperatures at depths of 0.1 and 0.4 m below the surface, wind speed, and wind direction. The data is complemented by **weather observations** performed twice to eleven times per day by the Japanese Meteorological Agency. Most of the ... : Resource Title: (a) Metadata Size: 113832 bytes Format: .zip URL: https://os.zhdk.cloud.switch.ch/envicloud/doi/envidat.540/a_Metadata.zip Description: General and specific metadata for all files. ...